One-year developmental changes in motor coordination and tennis skills in 10-12-year-old male and female tennis players - Tomasz Waldziński; Ewa Waldzińska; Aleksandra Durzyńska; Bartłomiej Niespodziński; Jan Mieszkowski; Andrzej Kochanowicz (BMC, 2024)
Abstract Background To date, no longitudinal studies of quarterly changes have been conducted on the differences in the development of motor coordination between boys and girls in relation to changes in their tennis skills level. Therefore, the aim of the study was to assess the development of motor coordination of 10-12-year-old tennis players over the course of 1 year, in the light of changes in tennis skills preparation. Methods One-hundred eighty male and female tennis players aged 10, 11, or 12 years old participated in the study. Each age group comprised 30 boys and 30 girls. To investigate their motor coordination development, a battery of general tests (simple reaction, complex reaction, Spalding test, spider test, hexagon jumping, Starosta's test, hand-eye test, balance, plate tapping, jump rope) and specific tennis skills tests (wall game and 100-tennis ball tests) were performed 4 times quarterly over 1 year. Differences between sexes and the time points were assessed. The rate of development evaluation was based on beta coefficient of linear regression. Results Boys generally performed better in tennis skills tests than girls. The boys performed better also in one motor coordination test (Spalding test) among 10-year-olds, in two additional tests (spider and plate tapping tests) among 11-year-olds, and another three more tests (simple reaction, complex reaction and Starosta's tests) among 12-year-olds. Jump rope test among 10-year-olds and hexagon jump test among 12-year-olds were the only tests where girls performed better than boys. On the other hand, girls showed higher rate of development in balance and complex reaction tests than boys. Conclusions We conclude that motor coordination and tennis skills development over 1 year is age-, sex-, and task-dependent, with the 10-12-year-old male tennis players performing better in tennis skills and overall motor coordination than females.